2008
DOI: 10.1007/s11695-008-9763-9
|View full text |Cite
|
Sign up to set email alerts
|

Argon Plasma Coagulation and Gastric Bypass—A Novel Solution to Stomal Dilation

Abstract: A patulous gastro-enterostomy after gastric bypass is a common cause of poor restriction and poor weight loss. Revisional surgery is an option but may be hazardous. This case report highlights the use of argon plasma coagulation by flexible endoscopy to reduce stomal size, improve restriction, and avoid revisional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…To cause greater tissue retraction and later reduction in anastomotic diameter owing to the greater depth of coagulation in the mucosa, we used a higher voltage (90 W) than that reported by Aly et al [13] (70 W). Similarly, given the high incidence of anastomotic ulcers observed at the beginning of this study, we used a longer between session interval (8 vs 6 weeks [13]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To cause greater tissue retraction and later reduction in anastomotic diameter owing to the greater depth of coagulation in the mucosa, we used a higher voltage (90 W) than that reported by Aly et al [13] (70 W). Similarly, given the high incidence of anastomotic ulcers observed at the beginning of this study, we used a longer between session interval (8 vs 6 weeks [13]).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, given the high incidence of anastomotic ulcers observed at the beginning of this study, we used a longer between session interval (8 vs 6 weeks [13]). The incidence of anastomotic ulcers was 10 % (three patients) observed in the second session, 10 % in third session (three patients, one of which had a persistent ulcer) and only 3 % (one patient, with ulcer in the third session but not the second) on final endoscopic evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APC is a noncontact photocoagulation method endoscopically applied to tissue after sedation in an outpatient setting [13]. In 2009, Aly [14] reported a case of APC in a patient with weight regain after RYGB that produced satisfactory results and concluded that this technique is effective and safe. Baretta et al [4] evaluated the safety and efficacy of APC in a study that included 30 patients with weight regain after RYGB who had dilatation of the gastrojejunal anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…desenvolviam estenoses esofágicas (Aly, 2009); idealizou então que a realização da ablação da mucosa na face gástrica da AGJ levaria à redução intencional do diâmetro da mesma; desta forma, esta técnica consiste na eletrocoagulação da mucosa sem contato direto com o tecido, através da qual a energia elétrica é aplicada ao ionizar-se gás de argônio; realiza-se o procedimento induzindo uma queimadura controlada em toda a circunferência da anastomose; o posterior processo cicatricial induz fibrose e consequentemente redução no seu diâmetro; o procedimento pode ser repetido até três vezes para que esta atinja o diâmetro desejado (Baretta et al, 2015). -Sutura endoscópica: a técnica de sutura endoscópica visando redução do diâmetro da AGJ foi descrita por Schweitzer (2004); baseava-se no racional então empregado no tratamento endoscópico da doença do refluxo gastroesofágico, através do estreitamento do cárdia com máquinas de sutura ou plicatura mecânica; basicamente, dois tipos de mecanismos de preensão tecidual eram utilizados: os de sucção e os de tração através de pinças, antes da passagem do ponto ou locação da plicatura; inicialmente, as máquinas de sutura atingiam apenas espessura parcial da parede, mas seu aprimoramento permitiu posteriormente que realizassem pontos de espessura total (atingindo até a camada serosa) (Kumar e Thompson, 2014); pontos de espessura total teoricamente possibilitariam suturas mais duradouras com força de tensão maior e consequentemente melhores resultados no tratamento do reganho de peso (Kumar et al, 2014a); assim, esta técnica envolve a aplicação de pontos ao redor da AGJ com auxílio de acessório de sutura acoplado geralmente a um gastroscópio terapêutico de duplo canal;…”
Section: O Tratamento Endoscópico Do Reganho De Pesounclassified